Особливості визначення часткових ємностей ізоляції трьожильних силових кабелів із застосуванням прямих вимірювань - Костюков, Іван Олександрович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Стаття присвячена дослідженню впливу додаткової складової паразитної індуктивності схеми вимірювання, що зумовлена необхідністю застосування додаткового провідника для усунення впливу паразитних ємностей досліджуваного шару ізоляції, на результати визначення часткових ємностей ізоляції трьохжильних силових кабелів в спільній металевій оболонці із застосуванням прямих вимірювань. Експериментальним шляхом показано, що наявність додаткової складової паразитної індуктивності призводить до резонансних явищ в схемі вимірювання та, як наслідок, до збільшення результатів прямих вимірювань часткових ємностей із зростанням частоти, що суперечить частотній залежності діелектричної проникності паперової ізоляції в розглянутому частотному діапазоні. Наведено схеми підключення вимірювачів імітансу із 3 клемами для прямих вимірювань часткових ємностей ізоляції трьохжильних силових кабелів в спільній металевій оболонці. The article is dedicated to the analysis of impact of the additional component of parasitic inductance of measuring circuit, which exists due to the necessity of applying the additional conductor in order to remove the influence of parasitic capacitances of the analyzed layer of insulation, on the results of determining the partial capacitances of insulation of three-core power cables in a common metal sheath by applying the direct measurements. It was experimentally shown that the existence of an additional component of parasitic inductance leads to resonance phenomena in the measuring circuit and, as a result, to the increasing of the results of the direct measurements of partial capacitances with the increasing of frequency, which contradicts the frequency dependence of dielectric permeability of paper insulation in the considered frequency range. Diagrams of connection of immittance meters with 3 terminals for direct measurements of partial capacitances of insulation in three-core power cables in a common metal sheath are presented. For the tested sample of power cable it was shows that at a frequency of 10 kHz, a high level of agreement is observed between the results of determining partial capacitances obtained by using the methods which require the applying of immittance meters with 2 and 3 terminals. This agreement is evidence that for the tested power cable design at a frequency of 10 kHz, the additional component of the inductance of the measurement circuit does not affect the results of measurements.
Specific properties of determination of partial capacitances of insulation in three-core power cables by applying the direct measurements
Keywords: паперова імпрегнована ізоляція; часткові ємності; тангенс кута діелектричних втрат; ізоляції силових кабелів; paper impregnated insulation; partial capacitances; dielectric dissipation factor; insulation of power cables